2019
DOI: 10.3390/su11154212
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Contributions to Sustainability: The Influence of Nature Play on Curiosity, Executive Function Skills, Creative Thinking, and Resilience

Abstract: Environmental education for young children has great potential for fostering the skills, values, and dispositions that support sustainability. While North American guidelines emphasize the importance of using the natural world for open-ended exploration, discovery, and play, this approach has been criticized for lacking the transformative power necessary for meaningfully contributing to sustainability issues. Four pilot studies were conducted exploring the influence of nature play in the context of nature pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 33 publications
5
54
0
5
Order By: Relevance
“…When looking at different factors simultaneously, we detected a positive association between children's knowledge of environmental sustainability issues and frequency of being outside in nature with parents. This is consistent with the results of a study where parents were reported by preschool children to be the major source of knowledge on the environmental impact of various transport modes in Sweden and the finding that playing in natural settings relates to skills that are linked to sustainability in children [43].…”
Section: Discussionsupporting
confidence: 91%
“…When looking at different factors simultaneously, we detected a positive association between children's knowledge of environmental sustainability issues and frequency of being outside in nature with parents. This is consistent with the results of a study where parents were reported by preschool children to be the major source of knowledge on the environmental impact of various transport modes in Sweden and the finding that playing in natural settings relates to skills that are linked to sustainability in children [43].…”
Section: Discussionsupporting
confidence: 91%
“…In its very definition [24], HNC describes a relationship with nature that encompasses many attributes already identified elsewhere in the academic literature. For example, the ability to be comfortable and curious about nature [49], the capacity to experiences awe and wonder [50], ecological literacy [51] and a connection with natural landscapes [52]. These attributes are aggregated in three distinguished and consecutive abilities: the ability to be in nature, with nature and for nature [24].…”
Section: Human-nature Relationships and Human-nature Connectionmentioning
confidence: 99%
“…These skills play a key role in the way we interact with family and peers, at school or at work. What is more, improving executive functioning are stated the foundation of the imagination and the creation of a desired future [77]. At the same time that the EFE-P program includes methodologies required for sustainable development, its basic principle is learning through play, which facilitates children's involvement and interaction with the world around them.…”
Section: Discussionmentioning
confidence: 99%